The pair of equations:
y = x + 4
y = -2x - 2
To solve the system of equation by substitution, you would substitute one variable for it's equivalent expression. Combining the pair of equations into one equation in only one variable. The easiest way to do this is by substituting out the variable y because it is already alone on one side of the equal sign. Substitute the y in the second equation for: x+4
x+4 = -2x - 2
solve for x
x + 2x = -2 -4
3x = -6
x = -2
now use the value for x to find y by putting into either equation.
y = x + 4
y = (-2) + 4
y = 2
solution is: (-2, 2)
Answer:
a 3x-7=12x
Step-by-step explanation:
=6.33333333
Linear functions? I'm pretty sure it means a reflection of a line
Answer:
D
Step-by-step explanation:
we first dilate it, making it the same size, then translate it to the right. I hope I have helped :)